Inhibitors of Serine Proteases in Regulating the Production and Function of Neutrophil Extracellular Traps - Majewski, Pawel; Majchrzak-Gorecka, Monika; Grygier, Beata; Skrzeczynska-Moncznik, Joanna; Osiecka, Oktawia; Cichy, Joanna (Frontiers in Immunology, 2016)
Neutrophil extracellular traps (NETs), DNA webs released into the extracellular environment by activated neutrophils, are thought to play a key role in the entrapment and eradication of microbes. However, NETs are highly cytotoxic and a likely source of autoantigens, suggesting that NET release is tightly regulated. NET formation involves the activity of neutrophil elastase (NE), which cleaves histones, leading to chromatin decondensation. We and others have recently demonstrated that inhibitors of NE, such as secretory leukocyte protease inhibitor (SLPI) and SerpinB1, restrict NET production in vitro and in vivo. SLPI was also identified as a NET component in the lesional skin of patients suffering from the auto-inflammatory skin disease psoriasis. SLPI competent NET-like structures (a mixture of SLPI with neutrophil DNA and NE) stimulated the synthesis of interferon type I (IFNI) in plasmacytoid dendritic cells (pDCs) in vitro. pDCs uniquely respond to viral or microbial DNA/RNA but also to nucleic acids of “self” origin with the production of IFNI. Although IFNIs are critical in activating the antiviral/antimicrobial functions of many cells, IFNIs also play a role in inducing autoimmunity. Thus, NETs decorated by SLPI may regulate skin immunity through enhancing IFNI production in pDCs. Here, we review key aspects of how SLPI and SerpinB1 can control NET production and immunogenic function.